Medical coatings and medical devices

A medical coating agent utilizing a polymer with a cyclic ether or cyclic carbonate structure addresses the issues of water solubility and unstable biocompatibility in existing agents, providing a stable, antithrombotic, and highly adhesive coating for medical devices.

JP7663197B2Active Publication Date: 2025-04-16TOAGOSEI CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021073210
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-23
Publication Date
2025-04-16
Estimated Expiration
2041-04-23

AI Technical Summary

Technical Problem

Existing medical coating agents for medical devices are either water-soluble, leading to potential elution when in contact with blood, or have insufficient adhesion and unstable biocompatibility with fluctuating antithrombotic properties over time.

Method used

A medical coating agent containing a polymer with a cyclic ether structure or a cyclic carbonate structure, which is water-insoluble and has excellent adhesion to the substrate, maintaining stable biocompatibility and consistent antithrombotic properties.

Benefits of technology

The proposed medical coating agent achieves antithrombotic and biocompatible properties that are stable over time, with high adhesion to the substrate and resistance to water solubility, thereby enhancing the performance and reliability of medical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663197000001
    Figure 0007663197000001
Patent Text Reader

Abstract

To provide a medical coating agent that has an antithrombotic ability and water-insolubility and also has high adhesion to a substrate, with little variation in the antithrombotic ability with time, leading to stable biocompatibility.SOLUTION: A medical coating agent contains a polymer containing a constitutional unit (A) derived from an ethylenic unsaturated monomer that contains a cyclic ether structure containing two or more oxygen atoms in a ring or a cyclic carbonate structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a medical coating agent and a medical device, and more particularly to a technique for imparting biocompatibility to a medical device that is used in contact with biological components or biological tissues. [Background technology]

[0002] Various materials such as synthetic polymers, ceramics, glass, metals, etc. are used as materials for medical devices. On the other hand, when a medical device comes into contact with a biological component or biological tissue, the body may recognize the medical device as a foreign body, which may inhibit the function of the medical device or affect the body. For example, in applications where a medical device is used in contact with blood, the body's defense function may be activated by the medical device being recognized as a foreign body, which may result in the formation of a blood clot. In view of this, attention has been paid to imparting biocompatibility to medical devices by using biocompatible synthetic polymers (see, for example, Patent Document 1 and Patent Document 2).

[0003] Patent Document 1 discloses that a polymer having a structural unit derived from 2-methacryloyloxyethyl phosphorylcholine is used as a coating component to impart biocompatibility to the surface of a medical device substrate. Patent Document 2 discloses that a polymer having a structural unit derived from 2-methoxyethyl acrylate is used as a biocompatible medical material. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2001 / 05855 [Patent Document 2] Japanese Patent Application Publication No. 04-152952 Summary of the Invention [Problem to be solved by the invention]

[0005] However, since the polymer having a structural unit derived from 2-methacryloyloxyethyl phosphorylcholine described in Patent Document 1 is water-soluble, there is a concern that the polymer coating the substrate surface of the medical device may dissolve into the blood during use in applications where the medical device is used in contact with blood. In addition, in order to prevent the polymer coating the substrate surface from dissolving into the blood, a complicated process such as chemically bonding the polymer to the substrate surface is required.

[0006] In addition, there are concerns that the polymer having a structural unit derived from 2-methoxyethyl acrylate described in Patent Document 2 does not have sufficient adhesion to a substrate and that its antithrombotic properties fluctuate over time, i.e., its stability in biocompatibility is poor.

[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a medical coating agent which has antithrombogenicity and water-insolubility, has excellent adhesion to a substrate, and exhibits stable biocompatibility with little change in antithrombogenicity over time. [Means for solving the problem]

[0008] According to the present invention, the following means are provided.

[0009] [1] A medical coating agent comprising a polymer containing a structural unit (A) derived from an ethylenically unsaturated monomer having a cyclic ether structure containing two or more oxygen atoms in the ring or a cyclic carbonate structure.

[0010] [2] The medical coating agent according to the above [1], wherein the polymer contains the structural unit (A) in an amount of 50 mass % or more based on the total structural units contained in the polymer. [3] The medical coating agent according to the above [1] or [2], wherein the polymer is a (meth)acrylic polymer. [4] A medical device having a substrate coated with any one of the medical coating agents according to [1] to [3] above. Effect of the Invention

[0011] The medical coating agent of the present invention has antithrombogenicity and water-insolubility, and has excellent adhesion to a substrate. In addition, the antithrombogenicity changes little over time, and the medical coating agent can exhibit stable biocompatibility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. In this specification, "(meth)acrylic" means acrylic and / or methacrylic, and "(meth)acrylate" means acrylate and / or methacrylate.

[0013] <Medical coating agent> The medical coating agent of the present invention contains a polymer (hereinafter also referred to as "polymer (P)") containing a structural unit (A) derived from an ethylenically unsaturated monomer having a cyclic ether structure containing two or more oxygen atoms in the ring or a cyclic carbonate structure. Each component contained in the medical coating agent of the present invention will be described below.

[0014] <Polymer (P)> The polymer (P) is a polymer having a structural unit derived from at least one monomer selected from the group consisting of an ethylenically unsaturated monomer having a cyclic ether structure containing two or more oxygen atoms in the ring (hereinafter also referred to as "monomer (A-1)") and an ethylenically unsaturated monomer having a cyclic carbonate structure (hereinafter also referred to as "monomer (A-2)"). The polymer (P) preferably has a cyclic ether structure or a cyclic carbonate structure containing two or more oxygen atoms in the ring (hereinafter also referred to as "specific cyclic structure") in the side chain, and specifically, it is preferable that the specific cyclic structure has a structure bonded to the main chain via a divalent linking group. By having the specific cyclic structure in the side chain, the polymer (P) becomes in a state containing a large amount of intermediate water upon hydration, which is considered to enable the polymer to exhibit good antithrombotic properties and stability over time.

[0015] Here, "intermediate water" refers to one form of the state of water that can be taken depending on the strength of the interaction with the polymer. In general, when a polymer is hydrated, the hydrated water takes the form of "free water" which has a weak interaction with the polymer and a freezing point of 0°C, "nonfreezing water" which has a strong interaction with the polymer and no detectable freezing point, and "intermediate water" which has an interaction with the polymer that is intermediate between free water and nonfreezing water and has a freezing point below 0°C. In other words, "intermediate water" refers to water that interacts with the polymer relatively slowly.

[0016] The cyclic ether structure of the monomer (A-1) is not particularly limited as long as it is a heterocyclic structure containing two or more oxygen atoms in the ring. The cyclic ether structure of the monomer (A-1) is preferably an oxygen-containing heterocyclic ring having 5 to 8 ring members, and examples thereof include a 1,3-dioxolane structure, a 1,2-dioxane structure, a 1,3-dioxane structure, a 1,4-dioxane structure, and a 1,3,5-trioxane structure. These cyclic structures may have a substituent such as an alkyl group having 1 to 5 carbon atoms introduced therein.

[0017] The cyclic carbonate structure of the monomer (A-2) is preferably an oxygen-containing heterocycle having 5 to 8 ring members, such as a 2-oxo-1,3-dioxolane structure, a 2-oxo-1,3-dioxane structure, etc. Into these cyclic structures, a substituent such as an alkyl group having 1 to 5 carbon atoms may be introduced.

[0018] The specific cyclic structure is more preferably a cyclic ether structure containing two or more oxygen atoms in the ring, in that it is superior in both water insolubility and stabilization of biocompatibility.

[0019] The monomer having the specific cyclic structure is preferably a (meth)acrylic monomer. When the monomer having the specific cyclic structure is a (meth)acrylic monomer, the reaction rate of the monomer can be easily increased, and the polymer obtained in the polymerization reaction can be used as a medical coating agent without purification, which is preferable.

[0020] Specific examples of monomers having a specific cyclic structure include monomer (A-1) such as (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, 2-vinyl-1,3-dioxolane, and 4,4,6-trimethyl-2-vinyl-1,3-dioxane.

[0021] Examples of the monomer (A-2) include (2-oxo-1,3-dioxolan-4-yl)methyl (meth)acrylate, 2-((2-oxo-1,3-dioxolan-4-yl)methoxy)ethyl (meth)acrylate, 4-vinyl-1,3-dioxolan-2-one, and 5-methyl-5-allyloxycarbonyl-1,3-dioxan-2-one.

[0022] The synthesis method of the monomer having a specific cyclic structure is not particularly limited. Examples of the synthesis method of the monomer having a specific cyclic structure include a method of reacting an acid chloride with an alcohol (acid chloride method); a method of transesterifying (meth)acrylate with a monohydric alcohol in the presence of a nitrogen-containing catalyst X and a zinc-containing catalyst Y; a method of reacting (meth)acrylic acid with an alcohol using sulfuric acid or a sulfonic acid as a catalyst; a method of transesterifying using an organic tin compound as a catalyst; a method of transesterifying using a titanium compound as a catalyst, and the like.

[0023] The polymer (P) is preferably a (meth)acrylic polymer, in that the specific cyclic structure is easily introduced into the side chain of the polymer and that it is easy to produce industrially. Specifically, the proportion of the structural units derived from the (meth)acrylic monomer among all the structural units derived from the monomers constituting the polymer (P) is preferably more than 50 mass%, more preferably 60 mass% or more, even more preferably 70 mass% or more, even more preferably 80 mass% or more, and even more preferably 90 mass% or more.

[0024] The polymer (P) may be composed of only structural units derived from a monomer having a specific cyclic structure, but may further have structural units derived from a monomer other than the monomer having the specific cyclic structure and copolymerizable with the monomer having the specific cyclic structure (hereinafter also referred to as "other monomers") within a range that does not impair the effects of the present invention. Examples of other monomers include unsaturated carboxylic acids, unsaturated acid anhydrides, (meth)acrylic acid alkyl esters, (meth)acrylic acid aliphatic cyclic esters, (meth)acrylic acid aromatic esters, (meth)acrylic acid alkoxyalkyl esters, (meth)acrylic acid hydroxyalkyl esters, polyalkylene glycol mono(meth)acrylates, vinyl compounds having a heterocyclic structure different from the specific cyclic structure, amino group-containing vinyl compounds, amide group-containing vinyl compounds, nitrile group-containing vinyl compounds, aromatic vinyl compounds, maleimide compounds, etc.

[0025] Specific examples of these include unsaturated carboxylic acids such as (meth)acrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, citraconic acid, cinnamic acid, succinic acid monohydroxyethyl (meth)acrylate, ω-carboxy-caprolactone mono(meth)acrylate, β-carboxyethyl (meth)acrylate, 4-carboxystyrene, etc. Examples of unsaturated acid anhydrides include maleic anhydride, itaconic anhydride, citraconic anhydride, etc.

[0026] Examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, hexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.

[0027] Specific examples of the aliphatic cyclic esters of (meth)acrylic acid include cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, isobornyl (meth)acrylate, adamantyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentanyl (meth)acrylate, etc. Specific examples of the aromatic esters of (meth)acrylic acid include phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxymethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, and 3-phenoxypropyl (meth)acrylate, etc.

[0028] Specific examples of (meth)acrylic acid alkoxyalkyl esters include methoxymethyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, n-propoxyethyl (meth)acrylate, n-butoxyethyl (meth)acrylate, methoxypropyl (meth)acrylate, ethoxypropyl (meth)acrylate, n-propoxypropyl (meth)acrylate, n-butoxypropyl (meth)acrylate, methoxybutyl (meth)acrylate, ethoxybutyl (meth)acrylate, n-propoxybutyl (meth)acrylate, and n-butoxybutyl (meth)acrylate.

[0029] Specific examples of the (meth)acrylic acid hydroxyalkyl ester include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate, etc. Examples of the polyalkylene glycol mono(meth)acrylate include polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and polyethylene glycol-polypropylene glycol mono(meth)acrylate, etc.

[0030] Examples of the vinyl compound having a heterocyclic structure different from the specific cyclic structure include glycidyl (meth)acrylate, (3,4-epoxycyclohexyl)methyl (meth)acrylate, and tetrahydrofurfuryl (meth)acrylate.

[0031] Examples of the amino group-containing vinyl compound include dimethylaminomethyl (meth)acrylate, diethylaminomethyl (meth)acrylate, 2-dimethylaminoethyl (meth)acrylate, 2-diethylaminoethyl (meth)acrylate, 2-(di-n-propylamino)ethyl (meth)acrylate, 2-dimethylaminopropyl (meth)acrylate, 2-diethylaminopropyl (meth)acrylate, 2-(di-n-propylamino)propyl (meth)acrylate, 3-dimethylaminopropyl (meth)acrylate, 3-diethylaminopropyl (meth)acrylate, and 3-(di-n-propylamino)propyl (meth)acrylate.

[0032] Examples of the amide group-containing vinyl compound include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, and N-methylol(meth)acrylamide.

[0033] Examples of the nitrile group-containing vinyl compound include cyanomethyl (meth)acrylate, 1-cyanoethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 1-cyanopropyl (meth)acrylate, 2-cyanopropyl (meth)acrylate, 3-cyanopropyl (meth)acrylate, 4-cyanobutyl (meth)acrylate, 6-cyanohexyl (meth)acrylate, 2-ethyl-6-cyanohexyl (meth)acrylate, 8-cyanooctyl (meth)acrylate, (meth)acrylonitrile, α-ethylacrylonitrile, α-isopropylacrylonitrile, α-chloroacrylonitrile, and α-fluoroacrylonitrile.

[0034] Examples of the aromatic vinyl compound include styrene, α-methylstyrene, β-methylstyrene, vinylxylene, methylstyrene, ethylstyrene, butylstyrene, methoxystyrene, hydroxystyrene, isopropenylphenol, vinylbenzoic acid, and vinylnaphthalene.

[0035] Examples of the maleimide compound include maleimide and N-substituted maleimide compounds. Examples of the N-substituted maleimide compound include N-alkyl-substituted maleimides such as N-methylmaleimide, N-ethylmaleimide, Nn-propylmaleimide, N-isopropylmaleimide, Nn-butylmaleimide, N-isobutylmaleimide, and N-tert-butylmaleimide; N-cycloalkyl-substituted maleimides such as N-cyclopentylmaleimide and N-cyclohexylmaleimide; N-aralkyl-substituted maleimides such as N-benzylmaleimide; and N-aryl-substituted maleimides such as N-phenylmaleimide, N-(4-hydroxyphenyl)maleimide, N-(4-acetylphenyl)maleimide, and N-(4-methoxyphenyl)maleimide. As the other monomer, one type may be used alone, or two or more types may be used in combination.

[0036] From the viewpoint of obtaining a water-insoluble and highly biocompatible polymer, the other monomer is preferably at least one selected from the group consisting of (meth)acrylic acid alkyl esters, aliphatic cyclic esters of (meth)acrylic acid, aromatic esters of (meth)acrylic acid, (meth)acrylic acid alkoxyalkyl esters, amino group-containing vinyl compounds, and amide group-containing vinyl compounds, and from the viewpoint of maintaining high antithrombotic properties even when a structural unit derived from another monomer is introduced, (meth)acrylic acid alkoxyalkyl esters are more preferable.

[0037] The polymer (P) preferably contains 30% by mass or more of the structural unit (A) based on the total structural units contained in the polymer (P). When the proportion of the structural unit (A) in the polymer (P) is within the above range, it is preferable that the substrate coated with the medical coating agent of the present invention can be provided with high antithrombogenicity, high adhesion to the substrate, and stable biocompatibility with little change in antithrombogenicity over time. The proportion of the structural unit (A) in the polymer (P) is more preferably 40% by mass or more, even more preferably 50% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, and even more preferably 90% by mass or more based on the total structural units contained in the polymer (P).

[0038] When the polymer (P) is a copolymer of a monomer having a specific cyclic structure and another monomer, the polymer (P) may be any of a random copolymer, a block copolymer, a graft copolymer, etc. From the viewpoint of uniformly introducing the specific cyclic structure into the entire polymer to enhance the effect of improving antithrombotic properties, among the above, a random copolymer is preferred.

[0039] The weight average molecular weight (Mw) of the polymer (P) is preferably in the range of 2,000 to 700,000. When Mw is 2,000 or more, the mechanical strength of the coating layer formed using the medical coating agent can be ensured. When Mw is 700,000 or less, the viscosity of the medical coating agent can be prevented from increasing, and the coatability and handleability can be ensured. The Mw of the polymer (P) is more preferably 5,000 or more, more preferably 8,000 or more, even more preferably 10,000 or more, and even more preferably 15,000 or more. The upper limit of the Mw of the polymer (P) is more preferably 500,000 or less, even more preferably 300,000 or less, and even more preferably 200,000 or less. In this specification, the Mw of the polymer is a standard polystyrene equivalent value obtained using gel permeation chromatography (GPC).

[0040] The polymerization method for producing the polymer (P) is not particularly limited. The polymer (P) can be obtained by polymerizing the monomers by adopting a known radical polymerization method such as solution polymerization, suspension polymerization, emulsion polymerization, bulk polymerization, etc. In the case of the solution polymerization method, for example, an organic solvent and a monomer are charged into a reactor, a polymerization initiator (e.g., an azo compound) is added, and the mixture is heated to 40 to 250°C to polymerize, thereby obtaining the desired polymer.

[0041] <Other ingredients> The medical coating agent of the present invention may further contain components other than the polymer (P) (hereinafter also referred to as "other components") depending on the purpose of use, etc. When the medical coating agent of the present invention is a liquid, one embodiment of the medical coating agent is a polymer composition in which the polymer (P) is dissolved or dispersed in a solvent as necessary.

[0042] As the solvent to be mixed in the medical coating agent of the present invention, an organic solvent capable of dissolving the polymer (P) is preferably used. Specific examples of the solvent contained in the medical coating agent of the present invention include alcohols such as methanol, ethanol, n-propanol, and isopropanol; ketones such as acetone and methyl ethyl ketone; ethers such as ethylene glycol monomethyl ether, propylene glycol monomethyl ether, tetrahydrofuran, and dioxane; esters such as ethylene glycol monomethyl ether acetate and ethyl acetate; amide solvents such as N,N-dimethylformamide (DMF) and N,N-dimethylacetamide; hydrocarbons such as n-hexane, cyclohexane, toluene, and xylene; and dimethyl sulfoxide. The solvent may be used alone or in combination of two or more.

[0043] Other components to be incorporated in the medical coating agent of the present invention include, in addition to the solvent, various drugs such as antibacterial agents, anti-inflammatory agents, and antioxidants. One or more of the other components may be used. The content of the other components may be appropriately selected according to each component within a range that does not impair the effects of the present invention.

[0044] In the medical coating agent of the present invention, the content of the polymer (P) is preferably 50 parts by mass or more, more preferably 70 parts by mass or more, even more preferably 80 parts by mass or more, even more preferably 90 parts by mass or more, and even more preferably 95 parts by mass or more, relative to 100 parts by mass of the total amount of solids contained in the medical coating agent (i.e., components other than the solvent in the medical coating agent). By setting the content of the polymer (P) within the above range, excellent antithrombotic properties are exhibited, and the antithrombotic properties fluctuate little over time, which is preferable in that more stable biocompatibility can be imparted to the substrate.

[0045] When the medical coating agent of the present invention is in a solution state, the solid content concentration in the medical coating agent (here, the ratio of the mass of the components other than the solvent in the medical coating agent to the volume of the solvent used in preparing the medical coating agent) is not particularly limited, but is preferably 0.001 to 30 (w / v)%. By setting the solid content concentration to 0.001 (w / v)% or more, a coating layer having sufficient thickness and mechanical strength can be formed on the substrate. When the solid content concentration is 30 (w / v)% or less, good coatability can be ensured, and a coating layer of uniform thickness can be easily formed. The solid content concentration in the polymer composition is more preferably 0.01 to 25 (w / v)%, and even more preferably 0.05 to 20 (w / v)%.

[0046] <Medical devices> The medical device of the present invention is formed by coating a substrate with the above-mentioned medical coating agent of the present invention. The medical device of the present invention has a part or all of its surface covered with the polymer (P) contained in the medical coating agent of the present invention, and therefore has excellent antithrombogenicity, exhibits little change in antithrombogenicity over time, and exhibits stable biocompatibility. In addition, since the polymer (P) is water-insoluble, it has high adhesion to the substrate even without surface modification of the substrate, and is suitable in that it can impart biocompatibility to the substrate surface of the medical device for a long period of time.

[0047] The substrate of the medical device to which the medical coating agent of the present invention is applied is not particularly limited. Examples of materials constituting the substrate include various materials such as resin, rubber, metal, glass, and ceramic. Among these, examples of resin include various resin materials such as polycarbonate, polyethylene terephthalate, polyvinyl chloride, polyethylene, polypropylene, polymethylpentene, polyurethane, poly(meth)acrylate, polystyrene, polyacetal, polysulfone, polyethersulfone, fluorine-based resins (polyvinylidene fluoride, polyethylene tetrafluoride, etc.), acrylonitrile-butadiene-styrene (ABS) resin, polyamide, and ethylene-vinyl acetate resin. Examples of rubber include silicone rubber and urethane rubber. Examples of metal include various metal materials such as stainless steel, titanium, and aluminum. The material constituting the substrate of the medical device may be a mixture of two or more materials.

[0048] The method for coating the substrate surface with the medical coating agent of the present invention is not particularly limited. For example, when the medical coating agent is in a solution state, the medical coating agent is applied to the substrate surface, and the solvent is removed by heating or other means to obtain a medical device in which at least a part of the substrate surface is coated with the polymer (P).

[0049] The coating method can be appropriately selected depending on the shape of the substrate, the purpose of use, etc. Examples of the coating method include various coating methods such as a bar coater, an applicator, a doctor blade, a dip coater, a roll coater, a spin coater, a flow coater, a knife coater, a comma coater, a reverse coater, a die coater, a lip coater, a gravure coater, a microgravure coater, and an ink jet. The coating amount of the medical coating agent can be appropriately selected depending on the application and material of the medical device so that the thickness of the coating layer formed by the medical coating agent is within a desired range.

[0050] The medical device whose substrate surface is coated with the medical coating agent of the present invention (i.e., the medical device of the present invention) is not particularly limited and can be applied to medical devices for various uses. The medical coating agent of the present invention can impart excellent antithrombotic properties and biocompatibility to the substrate surface, and therefore the medical coating agent of the present invention can be preferably applied as a material for coating the substrate of a medical device used in direct contact with blood. Specific examples of the medical device include various medical devices such as stents, catheters, blood bags, transfusion instruments, surgical instruments, dental instruments, blood circulation devices, blood purification devices, plasma separation devices, artificial blood vessels, and artificial organs (e.g., artificial heart-lung machines, artificial kidneys, etc.).

[0051] Here, the biocompatibility of a medical coating agent is considered to be related to the fact that the polymer material contained in the coating agent has intermediate water when the polymer contains water or is hydrated (see, for example, paragraphs 0003 and 0004 of JP 2016-35000 A). In the body, cells recognize foreign bodies, activating the body's defense mechanism and causing a rejection reaction. Therefore, when a medical device comes into contact with a biological component or biological tissue during treatment or surgery, if the body recognizes the medical device as a foreign body, the body's defense mechanism may be activated and may interfere with treatment. For example, if a medical device comes into contact with blood, a blood clot may be formed, inhibiting the function of the medical device or affecting the body. On the other hand, a polymer having intermediate water on its surface is less likely to be recognized as a foreign body by the body and can exhibit excellent biocompatibility.

[0052] The polymer (P) contained in the medical coating agent of the present invention has a specific cyclic structure and therefore tends to retain intermediate water during hydration. This is thought to enable the coating agent containing polymer (P) to exhibit excellent antithrombogenicity and stable biocompatibility with little fluctuation in antithrombogenicity over time. EXAMPLES

[0053] The present invention will be specifically described below based on examples. Note that the present invention is not limited to these examples. In the following, "parts" and "%" mean "parts by mass" and "% by mass", respectively, unless otherwise specified.

[0054] 1. Synthesis of ethylenically unsaturated monomer (a) [Synthesis Example 1: Synthesis of (2-oxo-1,3-dioxolan-4-yl)methyl acrylate] First, the raw material 4-(hydroxymethyl)-1,3-dioxolan-2-one (Sigma-Aldrich) was purified by distillation at 140° C. and 60 Pa. Into a 2 L four-neck flask, 47.2 g of 4-(hydroxymethyl)-1,3-dioxolan-2-one after distillation purification was added, along with 40.5 g of triethylamine and 1 L of ethyl acetate as a solvent. A mechanical stirrer was connected to the main tube, and a thermometer, dropping funnel, and three-way cock were connected to the side tube, and nitrogen was flowed at 100 mL / min. 40.7 g of acryloyl chloride was added to the dropping funnel of the side tube. The flask was then immersed in an ice bath to cool the internal temperature to 5°C or less. Acryloyl chloride was added dropwise from the dropping funnel, and the dropping rate was adjusted so that the internal temperature remained below 10°C. After the dropping was completed, the temperature was returned to room temperature and stirring was continued overnight. After stirring overnight, 300 mL of saturated aqueous sodium bicarbonate solution was added to the flask to stop the reaction. 300 mL of pure water was added and stirred, then transferred to a separatory funnel. The aqueous layer was removed and washed with 100 mL of saturated saline. Washing was performed three times. 100 mL of anhydrous sodium sulfate was added to the washed organic layer, and the mixture was stirred for 1 hour to dehydrate. After dehydration, 17.2 mg of paramethoxyphenol, which is the theoretical yield of 250 ppm, was added to the filtered organic layer. The solvent was then removed using a rotary evaporator. The recovered product was purified by silica gel column chromatography using a solvent of hexane / ethyl acetate mixed in a volume ratio of 1:1 to obtain (2-oxo-1,3-dioxolan-4-yl)methyl acrylate (hereinafter also referred to as "monomer (a1)"). The recovered amount of monomer (a1) was 15 g.

[0055] [Synthesis Example 2: Synthesis of 2-((2-oxo-1,3-dioxolan-4-yl)methoxy)ethyl acrylate] (1) Distillation purification of 3-(2-hydroxyethoxy)propane-1,2-diol 100 g of Emulgen GE-1 (Kao Corporation) was added to a 300 mL flask. A thermometer and a Liebig condenser were attached to the flask using an adapter, and two 100 mL flasks were connected as distillate receivers. A cooling liquid of -15°C was passed through the condenser, and reduced pressure distillation was carried out using a high vacuum pump. The temperature was adjusted to 125-140°C, and the internal pressure was adjusted to 7-25 Pa. After 48 hours, the distillation was stopped. After stopping, the main distillate 3-(2-hydroxyethoxy)propane-1,2-diol was 30 g, and the bottom liquid was 40 g.

[0056] (2) Synthesis of 4-((2-hydroxyethoxy)methyl)-1,3-dioxolan-2-one 20 g of the main distillate 3-(2-hydroxyethoxy)propane-1,2-diol recovered by distillation and 19.4 g of ethylene carbonate were added to a 100 mL two-neck flask. 0.02 g of activated alumina was added so that the amount was 0.1% by mass of the main distillate. A thermometer and a Dimroth condenser were connected to the flask, and a high vacuum pump was connected to the top via a three-way cock. With a cooling liquid at -15°C flowing through the condenser, the flask was heated to an internal temperature of 145°C and refluxed under reduced pressure at 30 Pa. After 14 hours, the reflux was stopped. After cooling, the internal liquid, 4-((2-hydroxyethoxy)methyl)-1,3-dioxolan-2-one, was recovered.

[0057] (3) Synthesis of 2-((2-oxo-1,3-dioxolan-4-yl)methoxy)ethyl acrylate Into a 1 L four-neck flask, 20 g of 4-((2-hydroxyethoxy)methyl)-1,3-dioxolan-2-one obtained in (2) above was added, along with 16.5 g of triethylamine and 300 mL of ethyl acetate as a solvent. A mechanical stirrer was connected to the main tube, a thermometer, a dropping funnel, and a three-way cock were connected to the side tube, and nitrogen was flowed at 100 mL / min. 14.7 g of acryloyl chloride was added to the dropping funnel of the side tube. The flask was then immersed in an ice bath to cool the internal temperature to below 5°C. Acryloyl chloride was added dropwise from the dropping funnel, and the dropping rate was adjusted so that the internal temperature was below 10° C. After the dropping was completed, the mixture was returned to room temperature and stirred overnight. After stirring overnight, 150 mL of a saturated aqueous solution of sodium hydrogen carbonate was added to the flask to stop the reaction. After further adding 150 mL of pure water and stirring, the mixture was transferred to a separatory funnel. After extracting the aqueous layer, 50 mL of saturated brine was added for washing. The washing was carried out 3 times. 50 mL of anhydrous sodium sulfate was added to the washed organic layer and stirred for 1 hour for dehydration. After dehydration, 6.7 mg of paramethoxyphenol, which was 250 ppm of the theoretical yield, was added to the filtered organic layer. Then, the solvent was removed using a rotary evaporator. The recovered product was purified by silica gel column chromatography using a solvent obtained by mixing hexane / ethyl acetate at a volume ratio of 1:1 to obtain 2-((2-oxo-1,3-dioxolan-4-yl)methoxy)ethyl acrylate (hereinafter also referred to as "monomer (a2)"). The recovered amount of monomer (a2) was 8.8 g.

[0058] 2. Production of polymer The weight-average molecular weight of the polymer was measured by gel permeation chromatography (GPC) analysis under the following measurement conditions. <Measurement conditions for GPC analysis> · Apparatus: HLC-8320GPC, manufactured by Tosoh Corporation · Detector: RI detector · Column: Use either of the following Column 1 or Column 2 Column 1: TSKgel SuperMultipore HZ-M, manufactured by Tosoh, 3 columns Column 2: TSKgel SuperHM-M, manufactured by Tosoh, 3 columns · Column temperature: 40 °C · Eluent: Use either of the following Eluent [1] or Eluent [2] Eluent [1]: Tetrahydrofuran (containing 0.03% sulfur as an internal standard), flow rate: 350 μL / min Eluent [2]: Dimethylformamide (containing 10 mM lithium bromide and 0.3 g / L acetone as an internal standard), flow rate: 300 μL / min · Calibration curve: A calibration curve was created using standard polystyrene.

[0059] [Production Example 1: Production of Polymer A] In a two-necked test tube, 3.0 g of (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl acrylate (Osaka Organic Chemical Industry Co., Ltd., hereinafter also referred to as "MEDOL-10"), 0.360 g of 2,2'-azobis(2-methylbutyronitrile) (Fujifilm Wako Pure Chemical Industries, Ltd., hereinafter also referred to as "V-59 initiator"), and 27 g of ethyl acetate were added. Then, a stirrer was placed in the test tube, a thermometer was attached to the side tube, and a three-way cock was attached to the main tube. A syringe needle was inserted into the three-way cock, and argon was blown into the solution at 100 mL / min for 30 minutes to deoxygenate it. Then, the three-way cock was closed. The test tube was inserted into a heat block set at 60° C. to initiate polymerization. The temperature of the heat block was then adjusted appropriately so that the internal temperature was 60° C. After 3 hours, the test tube was cooled in an ice bath to terminate polymerization. The reaction solution was purified twice by reprecipitation using a solvent in which hexane / acetone was mixed at a mass ratio of 9:1. The recovered polymer was then purified by reprecipitation using pure water as a solvent in the same manner to obtain polymer A. Polymer A was measured by GPC (using column 1 and eluent [1]) and found to have a weight average molecular weight of 153,000.

[0060] [Production Example 2: Production of Polymer B] In a two-necked test tube, 3.0 g of (2-oxo-1,3-dioxolan-4-yl)methyl acrylate obtained in Synthesis Example 1, 0.209 g of V-59 initiator, and 27 g of dimethyl sulfoxide were added. Then, a stirrer was placed in the test tube, a thermometer was attached to the side tube, and a three-way cock was attached to the main tube. A syringe needle was inserted into the three-way cock, and argon was blown into the solution at 100 mL / min for 30 minutes to deoxygenate it. Then, the three-way cock was closed. The test tube was inserted into a heat block set at 60° C. to initiate polymerization. The temperature of the heat block was then appropriately adjusted so that the internal temperature was 60° C. After 3 hours, the test tube was cooled in an ice bath to terminate polymerization. The reaction solution was purified by reprecipitation using a solvent in which methanol / dimethylformamide was mixed at a mass ratio of 4:6. Thereafter, the solvent was changed to pure water and the polymer B was obtained by reprecipitation. The polymer B was measured by GPC (using column 2 and eluent [2]) and found to have a weight average molecular weight of 86,000.

[0061] [Production Example 3: Production of Polymer C] 3.0 g of 2-((2-oxo-1,3-dioxolan-4-yl)methoxy)ethyl acrylate obtained in Synthesis Example 2, 0.167 g of V-59 initiator, and 27 g of dimethyl sulfoxide were added to a two-neck test tube. Then, a stirrer was placed in the test tube, a thermometer was attached to the side tube, and a three-way cock was attached to the main tube. A syringe needle was inserted into the three-way cock, and argon was blown into the solution at 100 mL / min for 30 minutes to deoxygenate it. Then, the three-way cock was closed. The test tube was inserted into a heat block set at 60° C. to initiate polymerization. The temperature of the heat block was then appropriately adjusted so that the internal temperature was 60° C. After 3 hours, the test tube was cooled in an ice bath to terminate polymerization. The reaction solution was purified by reprecipitation using a solvent in which methanol / dimethylformamide was mixed at a mass ratio of 4:6. Thereafter, reprecipitation was performed using pure water as the solvent to obtain polymer C. Polymer C was measured by GPC (using column 2 and eluent [2]) and found to have a weight average molecular weight of 75,000.

[0062] [Production Example 4: Production of Polymer D] 2.7g of MEDOL-10, 0.3g of 2-methoxyethyl acrylate (hereinafter also referred to as "MEA"), 0.360g of V-59 initiator, and 27g of ethyl acetate were added to a two-neck test tube. Then, a stirrer was placed in the test tube, a thermometer was attached to the side tube, and a three-way cock was attached to the main tube. A syringe needle was inserted into the three-way cock, and argon was blown into the solution at 100mL / min for 30 minutes to deoxygenate it. Then, the three-way cock was closed. The test tube was inserted into a heat block set at 60° C. to initiate polymerization. The temperature of the heat block was then appropriately adjusted so that the internal temperature was 60° C. After 3 hours, the test tube was cooled in an ice bath to terminate polymerization. The reaction solution was purified twice by reprecipitation using a solvent in which hexane / acetone was mixed at a mass ratio of 9:1. The recovered polymer was then purified by reprecipitation using pure water as the solvent in the same manner to obtain polymer D. Polymer D was measured by GPC (using column 1 and eluent [1]) and found to have a weight average molecular weight of 99,000.

[0063] [Production Example 5: Production of Polymer E] In a two-neck test tube, 1.8g of MEDOL-10, 1.2g of MEA, 0.360g of V-59 initiator, and 27g of ethyl acetate were added. Then, a stirrer was placed in the test tube, and a thermometer was attached to the side tube, and a three-way cock was attached to the main tube. A syringe needle was inserted into the three-way cock, and argon was blown into the solution at 100mL / min for 30 minutes to deoxygenate it. Then, the three-way cock was closed. The test tube was inserted into a heat block set at 60° C. to initiate polymerization. The temperature of the heat block was then adjusted appropriately so that the internal temperature was 60° C. After 3 hours, the test tube was cooled in an ice bath to terminate polymerization. The reaction solution was purified twice by reprecipitation using a solvent in which hexane / acetone was mixed at a mass ratio of 9:1. The recovered polymer was then purified by reprecipitation using pure water as the solvent in the same manner to obtain polymer E. The polymer E was subjected to GPC measurement (using column 1 and eluent [1]) and found to have a weight average molecular weight of 112,000.

[0064] [Production Example 6: Production of Polymer F] In a two-neck test tube, 1.5g of MEDOL-10, 1.5g of MEA, 0.360g of V-59 initiator, and 27g of ethyl acetate were added. Then, a stirrer was placed in the test tube, and a thermometer was attached to the side tube, and a three-way cock was attached to the main tube. A syringe needle was inserted into the three-way cock, and argon was blown into the solution at 100mL / min for 30 minutes to deoxygenate it. Then, the three-way cock was closed. The test tube was inserted into a heat block set at 60° C. to initiate polymerization. The temperature of the heat block was then appropriately adjusted so that the internal temperature was 60° C. After 3 hours, the test tube was cooled in an ice bath to terminate polymerization. The reaction solution was purified twice by reprecipitation using a solvent in which hexane / acetone was mixed at a mass ratio of 9:1. The recovered polymer was then purified by reprecipitation using pure water as a solvent in the same manner to obtain polymer F. Polymer F was measured by GPC (using column 1 and eluent [1]) and found to have a weight average molecular weight of 102,000.

[0065] [Comparative Production Example 1: Production of Polymer G] 3.0g of MEA, 0.555g of V-59 initiator, and 27g of ethyl acetate were added to a two-neck test tube. Then, a stirrer was placed in the test tube, a thermometer was attached to the side tube, and a three-way cock was attached to the main tube. A syringe needle was inserted into the three-way cock, and argon was blown into the solution at 100mL / min for 30 minutes to deoxygenate it. Then, the three-way cock was closed. The test tube was inserted into a heat block set at 60° C. to initiate polymerization. The temperature of the heat block was then appropriately adjusted so that the internal temperature was 60° C. After 3 hours, the test tube was cooled in an ice bath to terminate polymerization. The reaction solution was purified twice by reprecipitation using a solvent in which hexane / acetone was mixed at a mass ratio of 6:4. The recovered polymer was then purified by reprecipitation using pure water as the solvent in the same manner to obtain polymer G. Polymer G was measured by GPC (using column 1 and eluent [1]) and found to have a weight average molecular weight of 85,000.

[0066] 3. Manufacturing and evaluation of medical coating agents [Examples 1 to 6 and Comparative Example 1] <Evaluation method> (1) Antithrombotic properties Each of the obtained polymers was immersed in water for 3 days to allow it to absorb water. A predetermined amount of each polymer after absorption of water was taken, the surface moisture was removed using a medicine wrapping paper, and the polymer was spread thinly on the bottom of an aluminum pan. Using a differential scanning calorimeter (measuring device: DSC214Polyma manufactured by NETZSCH, measuring atmosphere: air atmosphere), the polymer was cooled from room temperature to -100°C and held for 10 minutes, and then heated at a rate of 5°C / min to confirm the presence or absence of a peak derived from the "intermediate water," and the antithrombotic properties were evaluated according to the following criteria. The results are shown in Table 1. ○: Peaks derived from intermediate water were confirmed (good antithrombotic properties) ×: No peak derived from intermediate water was confirmed (poor antithrombotic effect)

[0067] (2) Adhesion A 0.2 (w / v)% polymer solution (Example 1 and Comparative Example 1: methanol solution, Example 2 and Example 3: N,N-dimethylformamide (DMF) solution, Examples 4 to 6: ethyl acetate solution) was prepared and used as a medical coating agent. Next, a glass plate (Asahi Glass Co., Ltd., Fabritech FL11A, 1 mm thickness) and SUS304 (Engineering Test Service Co., Ltd., 1 mm thickness) were thoroughly washed with acetone, and then spin-coated with 650 μL of each medical coating agent on each plate. The spin-coating conditions were 500 rpm, 5 s → 1,500 rpm, 10 s → 1,500 to 4,000 rpm (slope), 5 s → 4,000 rpm, 10 s → 4,000 to 0 rpm (slope), 5 s. Then, the plate was dried at 100 ° C. for 30 minutes using a blower dryer to obtain a coating substrate for adhesion evaluation. The obtained coated substrate was observed visually, with an optical microscope, and with an atomic force microscope, and the adhesion was evaluated according to the following criteria. The results are shown in Table 1. ◯: In both the glass and SUS cases, the coating layer was not lifted and the surface was uniformly coated. △: Part of the coating layer was peeled off on glass and SUS. ×: In both the cases of glass and SUS, lifting was observed over the entire coating layer.

[0068] (3) Water contact angle A 0.2 (w / v)% polymer solution (Example 1 and Comparative Example 1: methanol solution, Example 2 and Example 3: DMF solution, Examples 4 to 6: ethyl acetate solution) was prepared and used as a medical coating agent. Next, a polyethylene terephthalate (PET) sheet (thickness: 125 μm, Mitsubishi Chemical Corporation DIAFOILT-100E) was thoroughly washed with acetone, and then 650 μL of each medical coating agent was used on the PET sheet and spin-coated under the same conditions as in (2) above. After that, the coated substrate for contact angle measurement was obtained by drying at 100° C. for 30 minutes using a blower dryer. The contact angle was measured for this coated substrate for contact angle measurement. The contact angle was measured by the water drop method using a contact angle measuring device (Eiko Seiki Co., Ltd., model number: SCA20). In the water drop method, a 2 μL water drop was brought into contact with the coating substrate for contact angle measurement at room temperature (relative humidity: approximately 40%), and the angle was measured immediately after dropping (0 seconds) and after a certain time (30 seconds after dropping, 60 seconds after dropping). Measurements were performed at three points on the same coating substrate for contact angle measurement, and the average value of the measurements at the three points was used. The results are shown in Table 1.

[0069] [Table 1]

[0070] 4. Evaluation Results As is clear from the results of Examples 1 to 6, the medical coating agents of Examples 1 to 6 containing the polymer (P) were confirmed to have antithrombotic properties, as a peak derived from intermediate water was observed in the evaluation by a differential scanning calorimeter. In addition, the water contact angle immediately after water was dropped onto the coating substrate for contact angle measurement was high at 75° or more in all of Examples 1 to 6, and it was confirmed that the coating agents had water insolubility. Furthermore, it was confirmed that the medical coating agents of Examples 1 to 6 had small changes in water contact angle over time, small fluctuations in antithrombotic properties over time (i.e., stable biocompatibility), and high adhesion to the substrate. In particular, it was confirmed that the use of polymer A having a cyclic ether structure containing two or more oxygen atoms in the ring was more excellent in terms of water insolubility and stabilization of biocompatibility compared to the use of polymers B and C having a cyclic carbonate structure (Examples 1 to 3).

[0071] In contrast, the medical coating agent of Comparative Example 1, which used a polymer not having a specific cyclic structure instead of the polymer (P), showed a large change in water contact angle over time and was unstable in biocompatibility. In addition, the coating layer formed using the coating agent of Comparative Example 1 had inferior adhesion to the substrate compared to Examples 1 to 6.

Claims

1. The polymer contains a structural unit (A) derived from an ethylenically unsaturated monomer having a cyclic ether structure containing two or more oxygen atoms in the ring or a cyclic carbonate structure, The polymer contains the structural unit (A) in an amount of 50 mass % or more based on all structural units contained in the polymer.

2. The medical coating agent according to claim 1 , wherein the polymer is a (meth)acrylic polymer.

3. A medical device comprising a substrate coated with the medical coating agent according to claim 1 or 2.

Citation Information

Patent Citations

  • Organism-compatible medical material

    JP1992152952A

  • Method for purifying (1,3-dioxoran-4-yl)alkyl alcohol

    JP2009286718A

  • Polymerizable and curable compositions for the preparation of polyvinyl alcohol-based biodegradable, biocompatible, and crosslinked polymers.

    JP2011505179A

  • Ultraviolet-curable coating composition, cured coat, and coated material

    JP2019059922A

  • Dioxanone-based copolymers for implantable devices

    US20150134048A1